Exchange rate pass-through: New evidence from German micro data - Eike Berner (Kiel University, Department of Economics, 2011)
This paper examines exchange rate pass-through into German import unit values over the last 20 years. I find incomplete pass-through to be the predominant characteristic for German imports with an average rate of 42% over three months. This result holds when considering monthly 8-digit data, the most disaggregated German import data available. Furthermore, I distinguish 16 German trading partners and estimate substantial cross-country differences in the pass-through to import unit values. Imports coming from European countries generally exhibit statistically zero pass-through. By contrast, non-European trading partners are characterized by statistically significant incomplete pass-through rates. I also study whether there are differences in the pass-through rates for appreciations and depreciations, as well as for small and large exchange rate shocks. Moreover, I test for a negative correlation between the goods' quality and its pass-through rate.
Keywords: F42; F31; F14; 330; exchange rate; pass-through; import prices; Germany